Simulation and experimental validation of heat and mass transfer during hot air drying of wheat grain piles using CFD-DEM under constant-variable temperature - Chen, Pengxiao; Chen, Jin; Fan, Mengke; Wang, Xiaowan; Lyu, Ruobing; Liu, Ye; Zhu, Wenxue; Wu, Jianzhang (International Journal of Agricultural and Biological Engineering, 2026)
Achieving rapid and uniform drying of wheat grain piles remains a major challenge because of the complex heat and mass transfer processes within the grain bulk. This study employs a hybrid discrete-continuous 3D model of a wheat grain heap to assess the effects of constant and variable temperature drying (46°C, 56°C, 46°C/16%/56°C, and 56°C/16%/46°C) on mass and heat transfer, as well as drying uniformity. Model validation against experimental data confirmed accuracy, with maximum relative errors below 15.6% for temperature and 4.63% for moisture content. For both constant and variable-temperature drying, the grain pile temperature exhibited a two-stage evolution, with a rapid increase during the initial stage followed by gradual temperature homogenization in the later stage as moisture migration became dominant. The early-stage temperature notably influences temperature and moisture uniformity. Results indicate that higher temperatures improve free water removal but slow its conversion to bound water. Prolonged high temperatures lead to epidermis contraction, internal deformation, and cracking. The findings suggest that variable temperature drying enhances overall drying efficiency and quality. These findings provide theoretical support and practical guidance for optimizing hot-air drying strategies and improving the energy efficiency and product quality of wheat grain drying. Keywords: wheat grain drying, constant and variable temperature drying, hot air drying, mass and heat transfer, drying process optimization DOI: 10.25165/j.ijabe.20261904.10040 Citation: Chen P X, Chen J, Fan M K, Wang X W, Lyu R, Liu Y, et al. Simulation and experimental validation of heat and mass transfer during hot air drying of wheat grain piles using CFD-DEM under constant-variable temperature. Int J Agric & Biol Eng, 2026; 19(4): 315–327.